PENDIDIKAN, KEMANDIRIAN, DAN PEMBANGUNAN BANGSA - Ruslan, Murniati (State Institute of Islamic Studies (IAIN) Palu, 2006)
It goes without saying that education plays a very significant and strategic role in a nation development. Many states in the world, in concerto, have no many natural resources, but can build themselves asÂ developed states. For example, Singapore, a Southeast Asian mini states that minus in natural resources. This state is successful in building itself as a prosper state of the world because it is supported by highly qualified human resources. It is necessary to elucidate, of course, that a qualified educational institution can produce qualified human resources. The reason is that education has not only a positive correlation with development, but also a rational way to create independence of society. This article elaborates educational matters, independence, and nation development.Â Kata Kunci : Pendidikan, kemandirian, pembangunan